Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Mariat Hotel di Kota Sorong - Sula D.S Benjamin; Meyta Longkotoy; Ade A Renouw (Journal on Education, 2023)
This study aims to analyze the effect of service quality on customer satisfaction at the Mariat Hotel in Sorong City. The data analysis method used is quantitative descriptive analysis. significant test through (t-test), using simple linear regression and coefficient of determination (R2). The population in this study were all customers of the Mariat Hotel in Sorong City. the sample amounted to 54 respondents. Primary data were obtained through interviews, questionnaires and documentation studies. From the results of data processing simple linear regression analysis using the SPSS for windows version 25 program, the regression equation Y = 4.239 + 0.840X, the regression coefficient value of 0.840 means that every time there is a change and an addition of one percent in the service quality variable, the Customer Satisfaction variable will increase. of 0.840 if the service quality variable is zero, then Customer Satisfaction has a value of 4.239. In the coefficient of determination test obtained R square 49.6%. meaning that the quality of service affects passenger satisfaction by 50.4%. while the remaining 41.4% is influenced by other factors not analyzed in this study. The results of the t-test, where tcount 7.157> from ttable 1.6939, it can be said that the service quality variable has a positive and significant effect on customer satisfaction.